MANAJEMEN KONFLIK PERTANAHAN : ALIH FUNGSI HUTAN ADAT DESA SUNGAI EKOK KECAMATAN RAKIT KULIM KABUPATEN INDRAGIRI HULU TAHUN 2010 - Raja Eric Rivilino; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Indonesia is a country with so many ethnic and indigenous therein, where it is estimated there are approximately 30 million people among them who live around the forest like the Talang Mamak tribe in Riau Province. Deforestation rate is so high and many alihfungsi forest to plantations or mining is an oppression against those who maintain forests for generations that became a local wisdom for them.This research was conducted in the village of River Raft Ekok Kulim District of Indragiri Hulu, which is the case in this thesis is the switch function Talang Mamak tribe indigenous forests into oil palm plantations aeral managed by a private company that is PT.Selantai Agro Lestari (SAL). Indigenous forest is actually set by the Government Indragiri Hulu along with the Regional Representatives Council Indragiri Hulu through SKB 31/SKB/II/2007 Number and Number 180/HK/II/2007 of 1800 hectares, thus causing conflict between communities and companies that establish oil palm plantations in the absence of land use permits (HGU) from the Ministry of Forestry. The study also looked at the efforts in the resolution of the conflict.This study used qualitative methods to conduct interviews and make observations to the study site in order to obtain data that would be material in this thesis.In the end, some conclusions can be drawn from the results of this study, namely, the establishment of oil palm plantations by private companies without any land use permits from the Ministry of Forestry, the presence of the sale and purchase of land by the public Talang Mamak, regional autonomy as the sustainability of forest destruction because, with facilitate the implementation of regional autonomy permits the release of such forestry Industrial Plantation Forest (HTI), Hak Guna Usaha (HGU) Mining License and others. Efforts in resolving this conflict is to report the conqueror fungsian indigenous forests to the Legislative Council Indragiri Hulu, through consultation and mediation through the National Land Agency.Keywords: Indigenous Forests, Transfer Function